The 5th International Congress of CiiEM (IC CiiEM) 2021
DOI: 10.3390/msf2021005018
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Aggressive Behavior: The Relation between the Five-Factor and Aggression Models in a Domestic Violence Suspects Sample

Abstract: The purpose of this study is to demonstrate the relationship between the five-factor model of personality and its association with aggression in 30 men and eight women who are suspects of domestic violence. The results show a positive correlation between neuroticism and hostility, a negative correlation between openness to experience and overall aggression, a negative correlation between agreeableness and physical aggression and anger, and a negative correlation between conscientiousness and anger. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…Previous criminal records were found in 14 (11%) DVOs and 31 (30%) OVOs, which is a statistically significant difference and suggests that the risk of re-offending is lower for DVOs. In previous studies concerning the relationship between criminal records and aggression on an intimate partner, Piquero et al revealed an association between these two elements [30], and Bauto et al found in their study that most of domestic violence perpetrators (65.8%) had previous criminal records [31]. This result was different to the one in this present study, which is probable because many cases of domestic violence remain unreported [8].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Previous criminal records were found in 14 (11%) DVOs and 31 (30%) OVOs, which is a statistically significant difference and suggests that the risk of re-offending is lower for DVOs. In previous studies concerning the relationship between criminal records and aggression on an intimate partner, Piquero et al revealed an association between these two elements [30], and Bauto et al found in their study that most of domestic violence perpetrators (65.8%) had previous criminal records [31]. This result was different to the one in this present study, which is probable because many cases of domestic violence remain unreported [8].…”
Section: Discussioncontrasting
confidence: 83%
“…Generally, according to Bauto et al, there is an interconditionality between neuroticism and aggressive behavior in the case of domestic violence suspects [31], and neuroticism is a predictor of many psychiatric pathologies [35]. With regard to psychiatric diagnoses in the cases of inmates who are incarcerated on homicide charges, previous studies have indicated an increased prevalence of schizophrenia [36][37][38], depression, personality disorders [37,39,40], affective disorders, and organic personality disorders [2].…”
Section: Discussionmentioning
confidence: 99%
“…Personality traits and childhood experiences have been shown to play a role in IPV perpetration. Genetic and epigenetic factors (Chester & DeWall, 2018) as well as personality traits have been found to explain IPV and aggressive behavior in general (Baúto et al, 2021;Sijtsema et al, 2014;Ulloa et al, 2016). In particular, agreeableness and neuroticism have been reported as drivers of IPV (Carton & Egan, 2017;Hines & Saudino, 2008;Kaighobadi et al, 2009).…”
Section: Effects Of Personality and Childhood Experiencesmentioning
confidence: 99%